2005
DOI: 10.1179/pom.2005.48.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mechanical properties direct from production components

Abstract: The ability to determine in situ mechanical properties of components would be of great value in monitoring the effect of processing condition excursions on service performance and for quality control. An approach to this problem based on testing small rectangular bars prepared directly from a component by water-jet cutting and subsequent grinding is presented. Impact resistance, tensile strength and transverse rupture strength values obtained from a PM synchroniser hub are consistent with those obtained for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…1 The considerable data accumulated on the mechanical properties of prealloyed Fe-Cr-Mo PM steels based on standard test specimens has been reviewed previously. 2…”
mentioning
confidence: 99%
“…1 The considerable data accumulated on the mechanical properties of prealloyed Fe-Cr-Mo PM steels based on standard test specimens has been reviewed previously. 2…”
mentioning
confidence: 99%
“…Solid state processing, in particular powder metallurgy, has been the preferred route for production of steel MMCs reinforced with TiB 2 , using commercially available TiB 2 powders or synthesised through the in-situ reaction of ferro-titanium and ferro-boron powders [6,7] or a master alloy composed of Fe-(50% TiB 2 + 50% Ti) [8] to avoid the production of undesirable brittle third phases such as Fe 2 B and TiC. The production of such phases is unavoidable when using other production routes such as liquid state processing [9,10] as it is very difficult to remove all impurities (such as oxygen) in the molten mix [7].…”
Section: Introductionmentioning
confidence: 99%
“…TiB 2 has been identified as an optimal reinforcement to use with iron-based matrices, not only because of its high stiffness (565 GPa) and low density (~4.53 g/cc) but also because it is in direct equilibrium with both the austenite and ferrite phases [5]. Solid state processing, in particular powder metallurgy, has been the preferred route for production of steel MMCs reinforced with TiB 2 , using commercially available TiB 2 powders or synthesised through the in-situ reaction of ferro-titanium and ferro-boron powders [6,7] or a master alloy composed of Fe-(50% TiB 2 + 50% Ti) [8] to avoid the production of undesirable brittle third phases such as Fe 2 B and TiC.…”
Section: Introductionmentioning
confidence: 99%
“…Oxide precipitates in another study have been shown to deteriorate the mechanical performance of the same PM alloy after sintering in high oxygen atmospheres. 18 However, as sintered oxygen contents were high in that case showing that the oxide reduction during sintering was insufficient.…”
Section: Discussionmentioning
confidence: 93%